Investigating glutamatergic mechanism in attention and impulse control using rats in a modified 5-choice serial reaction time task - Benn, A; Robinson, E (Public Library of Science, 2014)
The 5-choice serial reaction time task (5CSRTT) has been widely used to study attention and impulse control in rodents. In order to mimic cognitive impairments in psychiatry, one approach has been to use acute administration of NMDA antagonists. This disruption in glutamatergic transmission leads to impairments in accuracy, omissions, and premature responses although findings have been inconsistent. In this study, we further investigated glutamatergic mechanisms using a novel version of the 5CSRTT, which we have previously shown to be more sensitive to cognitive enhancers. We first investigated the effects of systemic treatment with NMDA antagonists. We also carried out a preliminary investigation using targeted medial prefrontal cortex infusions of a NMDA antagonist (MK801), mGluR2/3 antagonist (LY341495), and mGluR7 negative allosteric modulator (MMPIP). Acute systemic administration of the different NMDA antagonists had no specific effects on accuracy. At higher doses PCP, ketamine, and memantine, increased omissions and affected other measures suggesting a general disruption in task performance. Only MK801 increased premature responses, and reduced omissions at lower doses suggesting stimulant like effects. None of the NMDA antagonists affected accuracy or any other measures when tested using a short stimulus challenge. Infusions of MK801 had no effect on accuracy but increased premature responses following infralimbic, but not prelimbic infusion. LY341495 had no effects in either brain region but a decrease in accuracy was observed following prelimbic infusion of MMPIP. Contrary to our hypothesis, disruptions to glutamate transmission using NMDA antagonists did not induce any clear deficits in accuracy in this modified version of the 5CSRTT. We also found that the profile of effects for MK801 differed from those observed with PCP, ketamine, and memantine. The effects of MK801 in the infralimbic cortex add to the literature indicating this brain region and glutamate play an important role in impulse control.